Comity rules the day—complementary jurisdictional decisions in Jersey and Bermuda. Issue 5 (11th April 2018) - Robinson, Keith; Kistler, Andreas
Abstract: The courts of Jersey and Bermuda have recently been faced with competing applications concerning the same Bermuda law trust which is administered in Jersey. Far from the case reports showing a selfish tussle between these jurisdictions, they demonstrate a deep respect for comity. This article analyses the decisions in each jurisdiction and highlights the breadth of the jurisdiction of each court in trust matters and similarities in approach.